If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + 9x + -1 = -34 Reorder the terms: 12 + -1 + 9x = -34 Combine like terms: 12 + -1 = 11 11 + 9x = -34 Solving 11 + 9x = -34 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + 9x = -34 + -11 Combine like terms: 11 + -11 = 0 0 + 9x = -34 + -11 9x = -34 + -11 Combine like terms: -34 + -11 = -45 9x = -45 Divide each side by '9'. x = -5 Simplifying x = -5
| 5X+X+y+y+29=127 | | x-8=2x-18 | | 12+8-5n=42 | | -3b+10=-35 | | D-1/2=10 | | X-(X-5)=16 | | (d+2)(d-5)=-6 | | cosh(x)=1.25 | | 1524x-12+22x=5541+1124x-41 | | 4x-2=9+5(x-3) | | 3q+17+14=19 | | 29=7+x+2+x | | 2x+1+3x+5+6x-31=180 | | (3xy+2yx)3= | | 12-3x=66x | | x/80=35/100 | | X+(X-5)=16 | | 5y-4=3y-18 | | 70=x+4 | | 3x^4-16x^2-81=0 | | g(x)=3f(x+1)-1 | | 28=4n+4-8 | | 4(5x-1)-(x+5)=24 | | 7x+145.5=6 | | f(x)=16x^4+8x^2+1 | | tan(19pi/12 | | 0=-2t(8t-75) | | -28=4n+4-8 | | 11x+1=5x+61 | | f(-4)=x^2-3x+9 | | 29=7+x+2 | | 2l+28=58 |